Creative Edge Webcast : Adobe Photoshop CS6 New Features - Sylvan, Rob (Safari Books Online, 2012)
Join Rob Sylvan as he walks you through new features of Adobe Photoshop CS6, features that have the biggest impact on a photographer's workflow. Find out how this new version of Photoshop integrates with Lightroom 4 and is geared for today's photographers. This webcast will teach you to edit photos with the new Process Version 2012 in Camera Raw 7 and Lightroom 4 and how to seamlessly send photos back and forth between Lightroom and Photoshop.